Single or Combined Dietary Supply of Psidium guajava and Phyllanthus amarus Extracts Differentially Modulate Immune Responses and Liver Proteome in Striped Catfish (Pangasianodon hyphophthalmus) - Nhu, Truong Quynh; Bich Hang, Bui Thi; Cornet, Valérie; Oger, Mathilde; Bach, Le Thi; Anh Dao, Nguyen Le; Thanh Huong, Do Thi; Quetin-Leclercq, Joëlle; Scippo, Marie-Louise; Phuong, Nguyen Thanh; Kestemont, Patrick (Frontiers in Immunology, 2020)
Guava Psidium guajava L (Pg) and bhumi amla Phyllanthus amarus Schum. et Thonn (Pa) are well-known plants in traditional medicine. However, the capacity of these plants for improving the immune system of aquatic species has received less attention so far. This study aimed to investigate the effects of single supply or mixture of Pg and Pa extracts on immune responses, disease resistance and liver proteome profiles in striped catfish Pangasianodon hypophthalmus. Fish were fed diets including basal diet 0% or one of three doses of each plant extract, either alone or in mixture, 0.08, 0.2 or 0.5% Pg, Pa or mixture (Pg:Pa, v/v) for 6 weeks. The immune parameters (respiratory burst activity (RBA); nitric oxide synthase (NOS), total immunoglobulin, lysozyme and complement activities) were examined at W3, W6 post-feeding, and after challenge test. The growth parameters and the challenge test with Edwardsiella ictaluri were done at W6. The liver proteome profiles were analysed in W6 at 0.08% and 0.5% of each extract. The results showed that extract-based diets significantly improved growth parameters in the Pg0.2 group compared to control. The cellular immune responses in spleen and the humoral immune responses in plasma were significantly improved in a dose and time-dependent manner. Diets supplemented with single Pg and Pa extracts, and to lesser extent to combined extracts, could significantly decrease the mortality of striped catfish following bacterial infection compared to control. The proteomic results indicated that some pathways related to immune responses, antioxidant and lipid metabolism were enriched in liver at W6. Several proteins (i.e., CD8B, HSP90AA1, HSP90AB1, PDIA3, CASP8, TUBA1C, CCKAR, GNAS, GRIN2D, PLCG1, PRKCA, SLC25A5, VDAC2, ACTN4, GNAI2, LCK, CARD9, NLRP12, and NLRP3) were synergistically upregulated in mixture of Pg and Pa-based diets compared to control and single dietary treatments. Taken together, the results revealed that single Pg and Pa extracts at 0.2 and 0.5% and their mixture at 0.08 and 0.5% have the potential to modulate the immune mechanisms and disease resistance of striped catfish. Moreover, the combination of Pg and Pa in diets suggested positive synergistic effects liver proteome profile related to immune system processes.